Determining structural route components from GPS traces. (August 2016) - Knapen, Luk; Hartman, Irith Ben-Arroyo; Schulz, Daniel; Bellemans, Tom; Janssens, Davy; Wets, Geert
Highlights: The minimum number of cheapest subpaths which reconstitute a given path is determined. An efficient algorithm is specified, proved and applied to map matched GPS traces. Distributions for the minimum decomposition size are presented for several trace sets. The hypothesis that people tend to use a small number of shortest subpaths is verified. It is shown how to integrate the results in route choice set generation. Abstract: Analysis of GPS traces shows that people often do not use the least cost path through the transportation network while making trips. This leads to the question which structural path characteristics can be used to construct realistic route choice sets for use in traffic simulation models. In this paper, we investigate the hypothesis that, for utilitarian trips, the route between origin and destination consists of a small number of concatenated least cost paths. The hypothesis is verified by analyzing routes extracted from large sets of recorded GPS traces which constitute revealed preference information. Trips have been extracted from the traces and for each trip the path in the transportation network is determined by map matching. This is followed by a path decomposition phase for which the algorithm constitutes the first contribution of this paper. There are multiple ways to split a given path in a directed graph into a minimal number of subpaths of minimal cost. By calculating two specific path splittings, it is possible to identify subsets of the vertices ( splitVertexSuites ) that can be used to generate every possible minimum path splitting by taking one vertex from each such subset. As a second contribution, we show how the extracted information is used in microscopic travel simulation. The distribution for the size of the minimum decomposition, extracted from the GPS traces, can be used in constrained enumeration methods for route choice set generation . The sets of vertices that can act as boundary vertices separating consecutive route parts contain way points (landmarks) having a particular meaning to their user. The paper explains the theoretical aspects of route splitting as well as the process to extract splitVertexSuite s from big data. It reports statistical distributions extracted from sets of GPS traces for both multimodal person movements and unimodal car trips.